Molecular cloning and expression of the Bacillus anthracis edema factor toxin gene: a calmodulin-dependent adenylate cyclase. - Tippetts, M T (1988)
The Bacillus anthracis exotoxin is composed of a lethal factor, a protective antigen, and an edema factor (EF). EF is a calmodulin-dependent adenylate cyclase which elevates cyclic AMP levels within cells. The entire EF gene (cya) has been cloned in Escherichia coli, but EF gene expression by its own B. anthracis promoter could not be detected in E. coli. However, when the EF gene was placed downstream from the lac or the T7 promoter, enzymatically active EF was produced. The EF gene, like the protective antigen (pag) and lethal factor (lef) genes, was present on the large B. anthracis toxin plasmid pXO1.